Antibacterial Evaluation of Agarwood (Aquilaria malaccensis) Leaf Ethanol Extract Against Pathogenic Bacteria Using TLC-Bioautography - Marsaoly, Rivaldy (Journal Microbiology Science, 2024)
Pathogenic bacteria are microorganisms that live in the human body that cause disease, such as the bacteria bacillus subtilis, Pseudomonas aeruginosa, and Eschericia coli. compounds such as flavanoid compounds, alcolloids, saponins, tannins, and terpenoids that has antibacterial properties The purpose of this research was to determine the antibacterial activity of agarwood leaf ethanol extract (Aquilaria malaccensis) against pathogenic bacteria by TLC - bioautography. The results shown that agarwood leaf ethanol extract (Aquilaria malaccensis) has potential as antibacterial against, Pseudomonas aeruginosa, Bacillus subtilis, and Escherichia coli, with three active spots identified in the bioautogram profiles an Rf value of 0.20 demonstrated inhibition against Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli Additionally, Rf values of 0.50 and 0.36 exhibited inhibitory effects against Pseudomonas aeruginosa and Escherichia coli, highlighting the potential of agarwood leaf ethanol extract in combating pathogenic bacteria